International unification and national bibliography - Osvaldas Janonis (Knygotyra)
Every single bibliographic agency knows from its own experience that only nation-wide standards ensure the exchange of bibliographic data inside the country. The development of international co-operation requires the adoption of standards on the international level. The international unification guarantees the compatibility of bibliographic data and the possibility of universal access to it.